2015
DOI: 10.14393/bj-v31n2a2015-22504
|View full text |Cite
|
Sign up to set email alerts
|

Isolamento de Streptococcus agalactiae em diferentes órgãos de tilápias do nilo (Oreochromis niloticus) criadas em tanques-rede

Abstract: RESUMO:A estreptococose é uma das principais causas de mortalidade na criação de tilápias no Brasil, causando grandes perdas econômicas. Assim, o estudo objetivou determinar a frequência de isolamento e identificação por PCR de Streptococcus agalactiae em diferentes órgãos de tilápias do Nilo (Oreochromis niloticus) naturalmente infectadas, oriundas de oito pisciculturas da região norte do estado do Paraná que apresentavam sinais clínicos característicos de infecção estreptocócica. Para tanto, coletaram-se amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 24 publications
1
3
0
1
Order By: Relevance
“…niloticus with A. hydrophila at sites 1 and 3 with infection rates of 25% and 37.5%, respectively. S. agalactiae has been reported to cause large-scale outbreaks in cultured tilapia Thailand and Latin America (Marcusso et al, 2015). Furthermore, similar to the obtained findings regarding coinfection, Abdelsalam et al, (2017) 2006).…”
Section: Discussionsupporting
confidence: 79%
“…niloticus with A. hydrophila at sites 1 and 3 with infection rates of 25% and 37.5%, respectively. S. agalactiae has been reported to cause large-scale outbreaks in cultured tilapia Thailand and Latin America (Marcusso et al, 2015). Furthermore, similar to the obtained findings regarding coinfection, Abdelsalam et al, (2017) 2006).…”
Section: Discussionsupporting
confidence: 79%
“…As lesões internas são caracterizadas por congestão branquial, hepatomegalia e esplenomegalia acompanhada de congestão, ascite e encefalomalácea (Figura 1) (SALVADOR et al 2003, FIGUEIREDO et al 2006, TRABULSI & ALTERTHUM 2008, MARCUSSO et al 2015.…”
Section: Desenvolvimentounclassified
“…niloticus with A. hydrophila at sites 1 and 3 with infection rates of 25% and 37.5%, respectively. S. agalactiae has been reported to cause large-scale outbreaks in cultured tilapia Thailand and Latin America (Marcusso et al, 2015). Furthermore, similar to the obtained findings regarding coinfection, Abdelsalam et al, (2017) reported that S. agalactiae concurrently infected red hybrid tilapia reared in cement ponds in north coast, Egypt.…”
Section: Discussionmentioning
confidence: 52%